(untitled) (The Macau Ricci Institute Journal, 2023)
One of the attempts to establish the foundations of contemporary ethics is Paul Tillich’s existential analysis and evaluation of “the courage to be.” In humanity’s encounter or rather existential confrontation with the threat of nonbeing, revealed in the categories of space and time, finitude and freedom, and especially in experiencing guilt, absurdity, fear, doubts and other limitations of being, there is an opportunity for asking a question about the meaning of life and searching for sources of power in order to accept and overcome all these challenges. In the acceptance of being-itself the courage to be is born in a person, when they, realising and accepting their own finitude, overcome its limits and open themselves up to Infinity. This infinity of being-itself is not something abstract but is realised as Love, from which a person gets the courage to live in love, power and justice. As Pope Francis emphasizes: “Let us dream, then, as a single human family, as fellow travellers sharing the same flesh, as children of the same earth which is our common home, each of us bringing the richness of his or her beliefs and convictions, each of us with his or her own voice, brothers and sisters all.” (Pope Francis, 2020, no. 8)